English Taboo Words - Dwi Pebrina Sinaga; Marlina Tampubolon; Nurul Husnah Harahap (Jurnal Christian Humaniora, 2022)
Abstract:The title of this study is English Taboo Words. Taboo is something that is considered prohibited to be said or done in certain communities or cultures.As taboo is related to culture, then taboo in each country is different as the culture in each country is different too. This study found out that taboo in western countries, for example America, tends to relate with identity and sex while taboo in eastern countries tend to relate with belief/ myth. This finding is apparently because America is a country that valuably prefer knowledge to myth and is a developed and free country, so the taboos in this country are almost like swear words. They use taboo words to show which groups are superior and inferior, to degrade other people, and to humiliate them by mentioning their race or sex.